### One of Many Inverse TheoremsTweet

This article is inspired by a website, which is unfortunately has been down since around July 8, 2021. The website elaborately explained that both marginal distributions and conditional distributions of subvector of multivariate normal random variables given the remaining elements are indeed multivariate normal distributions as well. I feel obliged to write the content of the broken website in a blog which, hopefully, every learner can learn and benefit.

Before we show the previous statement is indeed true, there is the inverse of a matrix theorem which needs explaining.

Is that true that

$$$(A + CBD)^{-1} = A^{-1} - A^{-1} C (B^{-1} + DA^{-1} C)^{-1} D A^{-1}? \tag{1}\label{eq:the-theorem}$$$

#### Proof:

We need to prove that

$$$(A + CBD)(A + CBD)^{-1} = I \tag{2}\label{eq:first-part}$$$

and

$$$(A + CBD)^{-1}(A + CBD) = I \tag{3}\label{eq:second-part}$$$

where $I$ is an identity matrix.

We need to prove both Eq. \eqref{eq:first-part} and Eq. \eqref{eq:second-part} are true.

Firstly, let’s prove Eq. \eqref{eq:first-part} by using Eq. \eqref{eq:the-theorem} as follows:

\begin{align} (A + CBD)(A + CBD)^{-1} &= (A + CBD)(A^{-1} - A^{-1} C (B^{-1} + D A^{-1} C)^{-1} D A^{-1}) \\ &= (A + CBD)A^{-1} - (A + CBD) A^{-1} C (B^{-1} + D A^{-1} C)^{-1} D A^{-1} \\ &= I + CBDA^{-1} - (C + CBDA^{-1}C)(B^{-1} + DA^{-1}C)^{-1}DA^{-1} \\ &= I + CBDA^{-1} - CB(B^{-1} + DA^{-1}C)(B^{-1} + DA^{-1}C)^{-1}DA^{-1} \\ &= I + CBDA^{-1} - CBDA^{-1} \\ &= I. \end{align}

Secondly, let’s prove Eq. \eqref{eq:second-part} by employing Eq. \eqref{eq:the-theorem},

\begin{align} (A + CBD)^{-1}(A + CBD) &= (A^{-1} - A^{-1} C (B^{-1} + D A^{-1} C)^{-1} D A^{-1})(A+CBD) \\ &= A^{-1}(A + CBD) - A^{-1} C(B^{-1} + DA^{-1} C)^{-1} DA^{-1} (A + CBD) \\ &= I + A^{-1} CBD - A^{-1} C (B^{-1} + DA^{-1} C)^{-1} (D + DA^{-1} CBD) \\ &= I + A^{-1}CBD - A^{-1}C \underbrace{(B^{-1} + DA^{-1}C)^{-1} (B^{-1} + DA^{-1}C)}_{I} BD \\ &= I + A^{-1}CBD - A^{-1}CBD \\ &= I. \end{align}

Therefore, we have shown that this inverse theorem, Eq. \eqref{eq:the-theorem} is true.

Written on July 10, 2021